(untitled) (CIPEEX, 2022)
THE OBJECTIVE OF THIS WORK IS TO REPORT THE EXPERIENCE OF THE ACADEMICS OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA IN THE SOCIAL ACTION DEVELOPED AT THE DENTAL TEACHING CLINIC, WITH A FOCUS ON PROVIDING HEALTH EDUCATION IN A PLAYFUL AND CREATIVE WAY WITH THE CHILDREN PRESENT IN THE EVENT. THERE WAS ALSO THE PARTICIPATION OF THE STUDENTS OF THE MEDICINE COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGELICA ADDRESSING BLOOD GLUCOSE TESTS AND BLOOD PRESSURE MEASUREMENT. IN THE PRESENT PROJECT, THE AWARENESS OF THE NEED TO INTENSIFY ACTIONS LIKE THESE WAS PERCEPTIBLE, SINCE THE SENSATION OF BOTH ACADEMICS AND TEACHERS ABOUT THE ORAL HEALTH OF THOSE INVOLVED WERE DEFICIENT, IN WHICH THE MAJORITY PRESENTED RISKS OF ORAL DISEASES. THE METHODOLOGY WAS CARRIED OUT IN THEATERS HELD BY THE ACADEMICIANS ON THE IMPORTANCE OF ORAL HYGIENE, LISTENING TO MOMENTS OF RELAXATION WITH RANDOM JOKES IN THE WAITING ROOM AND ALSO THE USE OF LECTURES, WITH THE AIM OF GUIDING THE PUBLIC, ACCORDING TO THE EMINENT RISKS OF EACH ONE, WITH THE EVALUATION OF THE ORAL CAVITY IN BOTH ADULTS AND CHILDREN, TAKING THEM TO THE TOOTHBRUSH PRESENT IN THE CLINIC SO THAT THEY COULD PERFORM ORAL HYGIENE TECHNIQUES THAT WERE PREVIOUSLY ORIENTED. FACED WITH THE FACTS, THE FINAL SATISFACTION OF THE STUDENTS AND TEACHERS, WERE THE ACKNOWLEDGMENT AND RECOGNITION OF EACH INVOLVED IN THE PROJECT BY THE PATIENTS OF THE SOCIAL ACTION, EXEMPLIFYING THE INEXPLICABLE SATISFACTION OF THE MAJORITY INVOLVED IN THE PLANNING AND EXECUTION OF THIS PROJECT. WE OBTAINED AN ADULT AND CHILDREN POPULATION WITH THE CORRECT ORIENTATION FOR IMPROVEMENT IN THEIR QUALITY OF ORAL HEALTH. &NBSP; PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): HEALTH OF THE POPULATION. CHILD HEALTH. ORAL HEALTH.